Is Google Trends a useful tool for tracking mental and social distress during a public health emergency? A time–series analysis - Hannah Evans (Journal of Affective Disorders, 2021)
Background: Google Trends data are increasingly used by researchers as an indicator of population mental health, but few studies have investigated the validity of this approach during a public health emergency.Methods: Relative search volumes (RSV) for the topics depression, anxiety, self-harm, suicide, suicidal ideation, loneliness, and abuse were obtained from Google Trends. We used graphical and time-series approaches to compare daily trends in searches for these topics against population measures of these outcomes recorded using validated self-report scales (PHQ-9; GAD-7; UCLA-3) in a weekly survey (n=~70,000) of the impact COVID-19 on psychological and social experiences in the UK population (12/03/2020 to 21/08/ 2020).Results: Self-reported levels of depression, anxiety, self-harm/suicidal ideation, self-harm, loneliness and abuse decreased during the period studied. There was no evidence of an association between self-reported anxiety, self-harm, abuse and RSV on Google Trends. Trends in Google topic RSV for depression and suicidal ideation were inversely associated with self-reports of these outcomes (p=0.03 and p=0.04 respectively). However, there was statistical and graphical evidence that self-report and Google searches for loneliness (p<0.001) tracked one another. Limitations: No age/sex breakdown of Google Trends data are available. Survey respondents were not representative of the UK population and no pre-pandemic data were available. Conclusion: Google Trends data do not appear to be a useful indicator of changing levels of population mental health during a public health emergency, but may have some value as an indicator of loneliness. Keywords: Mental Health, Pandemic, Suicide, Depression, Loneliness, Anxiety, Domestic violence